“Krik? Krak!” and “Brother, I’m Dying” by Edwidge Danticat: The Transnational Experience of Haitian Refugees - Dudek, Mateusz (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2021)
KRIK? KRAK! AND BROTHER, I’M DYING BY EDWIDGE DANTICAT: THE TRANSNATIONAL EXPERIENCE OF HAITIAN REFUGEES The article offers an interpretation of a collection of short stories entitled Krik? Krak! and an autobiographical family memoir entitled Brother, I’m Dying by the Haitian-American author Edwidge Danticat. It concentrates on two interconnected issues: the transnationality of Haitian immigrants living in the United States and their hybrid identities interpreted in the context of the theory of identity in narrative. Selected works of Steven Vertovec, Anna De Fina, and Stuart Hall serve as the theoretical basis for the interpretation herein. The text sees the problems of migrating and living in a diaspora depicted by Danticat as phenomena important for developing transnational identities and producing narratives of identity-forming experiences. Moreover, the article presents an analysis of changing modes of cultural reproduction and dynamic identities of subsequent generations of Haitian immigrants. Additionally, the interpretation treats narratives of migration and diasporic life — often depicted by Danticat as belonging to the feminine sphere — as significant elements of the processes of putting together, rethinking, and reconstituting, through various modes of cultural reproduction, disjointed and disrupted Haitian identities. It also attempts to explore the techniques used by Danticat to build a coherent narrative of her family’s immigrant experiences and mediate her perspective on immigrant reality. KRIK? KRAK! I BROTHER, I’M DYING EDWIDGE DANTICAT: TRANSNARODOWE DOŚWIADCZENIA HAITIAŃSKICH UCHODŹCÓW Prezentowany artykuł proponuje interpretację zbioru opowiadań pt. Krik? Krak! oraz autobiograficznej powieści-memuaru pt. Brother, I’m Dying autorstwa haitańsko-amerykańskiej pisarki Edwidge Danticat. Tekst skupia się na dwóch połączonych problemach: transnarodowości haitańskich imigrantów żyjących w Stanach Zjednoczonych oraz ich hybrydowych tożsamościach interpretowanych w kontekście teorii tożsamości w narracji. Wybrane prace badaczy takich jak Steven Vertovec, Anna De Fina i Stuart Hall służą jako podłoże teoretyczne prezentowanej interpretacji. Postrzega ona problemy migracji i życia w diasporze opisywane przed Danticat jako zjawiska ważne dla rozwoju transnarodowych tożsamości i tworzenia narracji doświadczeń formujących tożsamość. Ponadto, prezentowany esej zawiera analizę zmieniających się metod kulturowej reprodukcji oraz dynamicznych tożsamości dalszych pokoleń haitańskich imigrantów. Dodatkowo, prezentowana interpretacja traktuje opowiadanie migracji i diasporycznego życia, które często jest przedstawiane przez Danticat jako należące do kobiecej sfery życia, jako znaczący element procesów ponownego łączenia, przemyśliwania i rekonstruowania poprzez różne metody kulturowej reprodukcji rozczłonkowanych i zakłóconych haitańskich tożsamości. Obecna analiza stara się również zbadać techniki użyte przez Danticat w celu skomponowania spójnych opowiadań dotyczących imigranckich doświadczeń swojej rodziny oraz przekazania swojego punktu widzenia na imigrancką rzeczywistość.